A survey of pediatric hematologists/oncologists' perspectives on single patient Expanded Access and Right to Try. Issue 1 (April 2021) - Chapman, Carolyn Riley; Belli, Hayley M; Leach, Danielle; Shah, Lesha D; Bateman-House, Alison
Introduction: Physicians in the United States play an essential role guiding patients through single patient pre-approval access (PAA) to investigational medical products via either the Food and Drug Administration (FDA)'s Expanded Access (EA) or the federal Right To Try (RTT) pathways. In this study, we sought to better understand pediatric hematologist/oncologists' attitudes about seeking PAA, on behalf of single patients, to investigational drugs outside of clinical trials. Methods: A cross-sectional survey was developed and sent to pediatric hematologist/oncologists via St. Baldrick's Foundation's email distribution list. Results: Of 73 respondents (10.1% of those who received the survey), 56 met eligibility criteria and are included in the analysis. Over 80% ( n  = 46) had prior experience with single patient PAA. Respondents were most concerned about the unknown risks and benefits of investigational drugs and financial implications of PAA for patients. One hundred percent and 91.1% of respondents indicated a willingness to support patients through EA and RTT pathways, respectively. When asked about their most recent experience with PAA, 40 out of 46 indicated that they used the FDA's EA pathway to seek PAA and 4 out of 46 indicated that they used the RTT pathway. Of 44 respondents who had used the EA or RTT pathway, 43 indicated that the biotechnology or pharmaceutical company they solicited granted access to the requested product. Conclusion: Survey results support other findings suggesting a need for additional physician support and education about PAA and that physicians may have unequal access to information about investigational drugs and concerns about financial implications of PAA for their patients.